Comprehensive systematic review on the self-gripping mesh vs sutured mesh in inguinal hernia repair - Anurag Singh, MRCS; Atreya Subramanian, MRCS; Wei H. Toh, MbChB; Premjithlal Bhaskaran, MD; Anam Fatima, MBBS; Muhammad S. Sajid, FRCS (Surgery Open Science, 2024)
Objective: The objective of this systematic review is to analyse the randomised control trials (RCTs) comparing the self-gripping mesh (SGM) with sutured mesh fixation (SMF) in open inguinal hernia repair. Materials and methods: RCTs comparing SGM with SMF in open inguinal hernia repair were selected from medical electronic databases and analysis was performed using the principles of meta-analysis with RevMan version 5 statistical software. Results: Seventeen RCTs involving 3863 patients were used for the final analysis. In the random effect model analysis, the operative time [mean difference − 7.72, 95 %, CI (−9.08, −6.35), Z = 11.07, P = 0.00001] was shorter for open inguinal hernia repair with SGM. However, there was noteworthy heterogeneity (Tau2 = 4.24; Chi2 = 1795.04, df = 12; (P = 0.00001; I2 = 99 %) among the included studies. The incidence of chronic groin pain [odds ratio 1.17, 95 %, CI (0.88, 1.54), Z = 1.09, P = 0.28], postoperative complications [odds ratio 0.92, 95 %, CI (0.73, 1.16), Z = 0.71, P = 0.48] and recurrence [odds ratio 1.31, 95 %, CI (0.80, 2.12), Z = 1.08, P = 0.28] were statistically similar between both groups, without heterogeneity. Conclusion: SGM failed to demonstrate a clinical advantage over SMF in terms of perioperative outcomes although the duration of surgery was shorter in SGM.